1994
DOI: 10.1111/j.1365-2230.1994.tb01200.x
|View full text |Cite
|
Sign up to set email alerts
|

A clinical evaluation of acne scarring and its incidence

Abstract: Despite scarring being a recognized sequel of acne, the actual extent and incidence of residual scarring remains unknown. One hundred and eighty-five acne patients were included in this study (101 females, 84 males). Patients were selected from acne clinics and their acne scarring was examined. The scarring was quantified according to a lesion count and allocated a score. The type and extent of scarring was correlated to the age and sex of the patient, the site of the acne, the previous acne grade according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
243
0
15

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(266 citation statements)
references
References 4 publications
8
243
0
15
Order By: Relevance
“…In Group B patients -individual scars were marked using a sterile marker pen. 23 gauge needle is inserted adjacent to the scar with the bevel upwards parallel to the skin surface, into the deep dermis under the scar to release fibrous bands at dermal or deep dermal subcutaneous plane (3)(4)(5) by moving needle in horizontal plane using the sharp edge of needle. Post procedure topical antibiotics were given for 5 days along with use of sunscreens (with a minimum sun protection factor of 30 and UVA 3+).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Group B patients -individual scars were marked using a sterile marker pen. 23 gauge needle is inserted adjacent to the scar with the bevel upwards parallel to the skin surface, into the deep dermis under the scar to release fibrous bands at dermal or deep dermal subcutaneous plane (3)(4)(5) by moving needle in horizontal plane using the sharp edge of needle. Post procedure topical antibiotics were given for 5 days along with use of sunscreens (with a minimum sun protection factor of 30 and UVA 3+).…”
Section: Methodsmentioning
confidence: 99%
“…2,3 Acne scarring is an unfortunate, permanent complication seen in about 95% patients of acne vulgaris up to some degree. 4,5 Given the psychological, social and emotional impact of disfigurement caused due to acne scars, dermatologists are frequently presented with the challenge of evaluating and providing treatment for the same. [6][7][8] The variation seen in development of scars is not As such, there are multiple modalities of treatment for acne scars.…”
Section: Introductionmentioning
confidence: 99%
“…Most patients had mixed type of acne scars compared to the study by Layton et al which showed more of ice pick scars. 8,9 In the study, improvement of scarring was assessed objectively along with photographs when compared to the studies done by Shim et al and Tsai et al where no grading was done. 5,10 Microdermabrasion showed good response in 9 patients with mild to moderate acne scars while remaining 31 patients failed to show any significant response.…”
Section: Discussionmentioning
confidence: 99%
“…Atrophic acne scars are by far the most common type. 4 Facial scars not only lead to cosme c problems, but also have psychological eff ects such as emo onal debilita on, embarrassment, poor self-esteem, and social isola on. 5 Many techniques are available for the correc on of atrophic acne scars, including subcision, dermabrasion, chemical peeling, laser technology, fat gra ing, and use of fi llers; however, these techniques have resulted in varying degrees of success and associated adverse eff ects.…”
Section: Introductionmentioning
confidence: 99%